MORPHOLOGICAL REDUPLICATION OF BODO AND ASSAMESE - Dr. Ranjita Boro (Journal of Population Therapeutics and Clinical Pharmacology, 2022)
In linguistic studies, Reduplication generally means the repetition of any linguistic unit such as a Phoneme, Morpheme, Word, Phrase, Clause or the utterance. Reduplication is also used in inflections to convey a grammatical function, such as plurality, intensification etc. and in lexical derivation to create new words. Reduplication is a word formation process in which some part of a base (a segment, syllable, morpheme) is repeated, either to the initial or as prefix, or to the final or as suffix of the basic word or, occasionally, within the middle of the basic word. Morphological reduplication is also a type of Reduplication.